Expression of Angiotensin II Receptor 2 in Microcystic Lymphatic Malformation. Issue 3 (5th August 2021) - Siljee, Sam Duro; Gower, Alexandra; Brasch, Helen Dian; Patel, Josie; Bockett, Nicholas; Itinteang, Tinte; Tan, Swee Thong
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To investigate the presence of components of the renin-angiotensin system (RAS) on the embryonic stem cell (ESC)–like population in microcystic lymphatic malformation (mLM). Methods: mLM tissue samples from 18 patients underwent immunohistochemical staining for RAS components including angiotensinogen, renin, prorenin receptor (PRR), angiotensin-converting enzyme (ACE), ACE2, and angiotensin II receptor 2 (AT2 R). Snap-frozen mLM tissues from 6 of the patients were used to confirm protein expression by western blotting for angiotensinogen, PRR, ACE, ACE2, and AT2 R. Reverse transcription quantitative polymerase chain reaction was used to detect transcript expression of angiotensinogen, renin, PRR, ACE, ACE2, AT1 R, and AT2 R in 5 of the mLM tissue samples. Results: Immunohistochemical staining demonstrated expression of AT2 R in all, and PRR in 1, while angiotensinogen, renin, ACE, and ACE2 were not observed in any of the 18 mLM samples. Western blotting showed expression of angiotensinogen, PRR, and ACE, but not ACE2 or AT2 R in all 6 mLM tissue samples. Reverse transcription quantitative polymerase chain reaction demonstrated transcript expression of angiotensinogen, PRR, ACE, and ACE2 in all, AT1 R in 4, AT2 R in 2, and renin in 1 of the 5 mLM tissue samples. Immunofluorescence dual-staining in 2 mLM tissue samples demonstrated expression of AT2 R on the OCT4+ cells. Conclusion: This study shows expression of angiotensinogen, PRR, ACE. ACE2, AT1 R, and AT2 R transcripts and AT2 R protein, in mLM tissue samples, with AT2 R localizing to the OCT4+ ESC-like population. This suggests the ESC-like population may be a novel therapeutic target by modulation of the RAS.